High‐Quality Whispering‐Gallery‐Mode Lasing from Cesium Lead Halide Perovskite Nanoplatelets. (1st July 2016) - Zhang, Qing; Su, Rui; Liu, Xinfeng; Xing, Jun; Sum, Tze Chien; Xiong, Qihua
Abstract : Semiconductor micro/nano‐cavities with high quality factor (Q) and small modal volume provide critical platforms for exploring strong light‐matter interactions and quantum optics, enabling further development of coherent and quantum photonic devices. Constrained by exciton binding energy and thermal fluctuation, only a handful of wide‐band semiconductors such as ZnO and GaN have stable excitons at room temperature. Metal halide perovskite with cubic lattice and well‐controlled exciton may provide solutions. In this work, high‐quality single‐crystalline cesium lead halide CsPbX3 (X = Cl, Br, I) whispering‐gallery‐mode (WGM) microcavities are synthesized by vapor‐phase van der Waals epitaxy method. The as‐grown perovskites show strong emission and stable exciton at room temperature over the whole visible spectra range. By varying the halide composition, multi‐color (400–700 nm).WGM excitonic lasing is achieved at room temperature with low threshold ( 2.0 μJ cm −2 ) and high spectra coherence ( 0.14–0.15 nm). The results advocate the promise of inorganic perovskites towards development of optoelectronic devices and strong light‐matter coupling in quantum optics. Abstract : High‐quality cesium lead halide nanoplatelets functioning as whispering‐gallery‐mode microcavities are synthesized by vapor‐phase van der Waals epitaxy method. Multicolor, low‐threshold excitonic lasing action with a high spectra coherence of 0.14–0.15 nm is realized at room temperature. The findings are not only important for developing on‐chip small lasers and high‐speed exciton devices but also promising for fundamental studies in cavity quantum electrodynamics.